“Umlaut” as a Terminological Reflection of Interlanguage Relations in Linguistics - Andrey V. Ivanov (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The article examines the history of appearance of the term "umlaut" in the terminology of Russian linguistics. Using the methods of historical-linguistic, definitional and semantic analysis of scholarly and scientific-theoretical sources (grammars, grammar treatises and dictionaries) published in Russia in the period from the late 18 th century to the mid 20 th century, the author traces the evolution of the phonetic status of umlaut. It was ascertained that in the 18 th century, in line with the traditions, established by the German grammarians, umlaut was first considered a diphthong, since it was widely believed to be a combination of two sounds pronounced together. It is shown that in the late 18 th century, the approach to the evaluation of the umlaut's status begins to change. This is to be explained by the change of scientific and linguistic paradigm in Russian linguistics. The facts of terminological variation are revealed and characterized. In the course of its existence, the term "umlaut", which entered Russian linguistic terminology only by the end of the first third of the 20 th century, received several one-word or compound names: "ogolosok" (1799), "peremena glasnykh" (vowel change) (1844), "perezvuk" (1845), "pereglasovka" (1857), "sliyaniye glasnykh" (vowel fusion) (1864), "izmeneniye glasnykh" (vowel mutation) (1871), "pereglasovaniye" (1882), "suzhivaniye glasnykh" (vowel narrowing) (1895). Until now, only the synonym "pereglasovka" has been preserved.